Comparative characterization of the HGF/Met and MSP/Ron systems in primary pancreatic adenocarcinoma. (November 2019) - Vanderwerff, Brett R.; Church, Kevin J.; Kawas, Leen H.; Harding, Joseph W.
Highlights: BxPC-3 cells co-express the Met and Ron receptors on a single cell level. HGF and MSP increase BxPC-3 cell migration, but only HGF increases proliferation. MSP mimics a subset of the transcriptional effects driven by HGF in BxPC-3 cells. High Met expression reduces pancreatic cancer patient survival independent of Ron. Abstract: Pancreatic cancer is an aggressive disease with a poor prognosis for which current standard chemotherapeutic treatments offer little survival benefit. Receptor tyrosine kinases (RTK)s have garnered interest as therapeutic targets to augment or replace standard chemotherapeutic treatments because of their ability to promote cell growth, migration, and survival in various cancers. Met and Ron, which are homologous RTKs activated by the ligands hepatocyte growth factor (HGF) and macrophage stimulating protein (MSP), respectively, are over-activated and display synergistic malignant effects in several cancers. Despite the homology between Met and Ron, studies that have directly compared the functional outcomes of these systems in any context are limited. To address this, we sought to determine if the HGF/Met and MSP/Ron systems produce overlapping or divergent contributions towards a malignant phenotype by performing a characterization of MSP and HGF driven signaling, behavioral, and transcriptomic responses in a primary pancreatic adenocarcinoma (PAAD) cell line in vitro . The impact of dual Met and Ron expression signatures on the overall survival of PAAD patients was also assessed. We found HGF and MSP both encouraged PAAD cell migration, but only HGF increased proliferation. RNA sequencing revealed that the transcriptomic effects of MSP mimicked a narrow subset of the responses induced by HGF. Analysis of clinical data indicated that the strong prognostic value of Met expression in primary PAAD does not appear to be modulated by Ron expression. The relatively reduced magnitude of MSP-dependent effects on primary PAAD cells are consistent with the limited prognostic value of Ron expression in this cancer when compared to Met. Although HGF and MSP produced a differing breadth of responses in vitro, overlapping pro-cancer signaling, behavioral, and transcriptional effects still point to a potential role for the MSP/Ron system in pancreatic cancer.